Academic Talent Management of High-Achieving Students in Competition-Based Nonformal Education: Integrating Higher Order Thinking Skills and Deep Learning (A Case Study of Olimnus) (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: Incidental, outcome-oriented coaching practices have often shaped the development of high-achieving students without fully supporting sustainable academic talent management. This study aims to analyze academic talent management in nonformal education by integrating educational competitions, higher-order thinking skills (HOTS), and deep learning. Method: This research employed a qualitative case study design conducted at Olimnus, a provider of competition-based nonformal education. Data collection involved document analysis, observations, and in-depth interviews with administrators and high-achieving students. They were systematically analyzed using a thematic analysis approach to identify key patterns and themes. Result: The findings indicate that educational competitions at Olimnus serve not as event-based activities, but as management tools for academic talent development, including planning, identification, development, evaluation, and sustainability. The integration of HOTS in assessment design and academic coaching serves as a core mechanism for developing students’ analytical, evaluative, and reflective thinking skills. Well-planned, HOTS-based talent management practices foster deep learning, as reflected in shifts in students’ learning orientations toward conceptual understanding, critical reflection, and independent learning. Novelty: This study offers a novel contribution by proposing an integrative model of academic talent management in nonformal education that connects educational competitions, HOTS, and deep learning within a sustainable managerial cycle. This contribution extends the understanding of academic talent management beyond formal education settings and offers practical implications for designing systematic, sustainable, competition-based talent development strategies.